Vaccination Against Seasonal or Pandemic Influenza in Emergency Medical Services. Issue 2 (9th February 2016) - Moser, Alexandre; Mabire, Cédric; Hugli, Olivier; Dorribo, Victor; Zanetti, Giorgio; Lazor-Blanchet, Catherine; Carron, Pierre-Nicolas
Abstract: Introduction: Influenza is a major concern for Emergency Medical Services (EMS); EMS workers' (EMS-Ws) vaccination rates remain low despite promotion. Determinants of vaccination for seasonal influenza (SI) or pandemic influenza (PI) are unknown in this setting. Hypothesis: The influence of the H1N1 pandemic on EMS-W vaccination rates, differences between SI and PI vaccination rates, and the vaccination determinants were investigated. Methods: A survey was conducted in 2011 involving 65 Swiss EMS-Ws. Socio-professional data, self-declared SI/PI vaccination status, and motives for vaccine refusal or acceptation were collected. Results: Response rate was 95%. The EMS-Ws were predominantly male (n=45; 73%), in good health (87%), with a mean age of 36 (SD=7.7) years. Seventy-four percent had more than six years of work experience. Self-declared vaccination rates were 40% for both SI and PI (PI+/SI+), 19% for PI only (PI+/SI-), 1.6% for SI only (PI-/SI+), and 39% were not vaccinated against either (PI-/SI-). Women's vaccination rates specifically were lower in all categories but the difference was not statistically significant. During the previous three years, 92% of PI+/SI+ EMS-Ws received at least one SI vaccination; it was 8.3% in the case of PI-/SI- ( P =.001) and 25% for PI+/SI- ( P =.001). During the pandemic, SI vaccination rate increased from 26% during the preceding year to 42% ( P =.001). Thirty percent of the PI+/SI+ EMS-Ws declared that they would not get vaccination next year, while this proportion was null for the PI-/SI- and PI+/SI- groups. Altruism and discomfort induced by the surgical mask required were the main motivations to get vaccinated against PI. Factors limiting PI or SI vaccination included the option to wear a mask, avoidance of medication, fear of adverse effects, and concerns about safety and effectiveness. Conclusion: Average vaccination rate in this study's EMS-Ws was below recommended values, particularly for women. Previous vaccination status was a significant determinant of PI and future vaccinations. The new mask policy seemed to play a dual role, and its net impact is probably limited. This population could be divided in three groups: favorable to all vaccinations; against all, even in a pandemic context; and ambivalent with a "pandemic effect." These results suggest a consistent vaccination pattern, only altered by exceptional circumstances. A Moser, C Mabire, O Hugli, V Dorribo, G Zanetti, C Lazor-Blanchet, PN Carron .Vaccination against seasonal or pandemic influenza in Emergency Medical Services .Prehosp Disaster Med .2016 ;31 (2 ):155 –162 .